Study protocol for SPARED trial: randomised non-inferiority phase III trial comparing dexamethasone on day 1 with dexamethasone on days 1–4, combined with neurokinin-1 receptor antagonist, palonosetron and olanzapine (5 mg) in patients receiving cisplatin-based chemotherapy. Issue 12 (17th December 2020) - Minatogawa, Hiroko; Izawa, Naoki; Kawaguchi, Takashi; Miyaji, Tempei; Shimomura, Kazuhiro; Kazunori, Honda; Iihara, Hirotoshi; Ohno, Yasushi; Inada, Yusuke; Arioka, Hitoshi; Morita, Hajime; Hida, Naoya; et al.
Abstract : Introduction: Dexamethasone (DEX) is administered for multiple days to prevent chemotherapy-induced nausea and vomiting for patients receiving highly emetogenic chemotherapy (HEC); however, its notorious side effects have been widely reported. Although our multicentre randomised double-blind comparative study verified non-inferiority of sparing DEX after day 2 of chemotherapy when combined with neurokinin-1 receptor antagonist (NK1-RA) and palonosetron (Palo) for patients receiving HEC regimen, DEX sparing was not non-inferior in patients receiving cisplatin (CDDP)-based HEC regimens in subgroup analysis. Recently, the efficacy of the addition of olanzapine (OLZ) to standard triple antiemetic therapy on HEC has been demonstrated by several phase III trials. This study aims to confirm non-inferiority of DEX sparing when it is combined with NK-1RA, Palo and OLZ in patients receiving CDDP-based HEC regimens. Methods and analysis: This is a randomised, double-blind, phase III trial. Patients who are scheduled to receive CDDP ≥50 mg/m 2 as initial chemotherapy are eligible. Patients are randomly assigned to receive either DEX on days 1–4 or DEX on day 1 combined with NK1-RA, Palo and OLZ (5 mg). The primary endpoint is complete response (CR) rate, defined as no emesis and no rescue medications during the delayed phase (24–120 hours post-CDDP administration). The non-inferiority margin is set at −15.0%. We assume that CR rates would be 75% in both arms. Two hundred and sixty-two patients are required for at least 80% power to confirm non-inferiority at a one-sided significance level of 2.5%. After considering the possibility of attrition, we set our final required sample size of 280. Ethics and dissemination: The institutional review board approved the study protocol at each of the participating centres. The trial result will be presented at international conferences and published in peer-reviewed journals. Trial registration number: UMIN000032269.